2008
DOI: 10.1111/j.1574-6968.2008.01178.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of the biological control agentBacillus thuringiensison the indigenous microbial community within the pepper plant phyllosphere

Abstract: Although biological control agents (BCAs) have been used extensively for controlling insects and pathogens of plants, little is known regarding the effects of such agents on the indigenous microbial communities within the plant phyllosphere. We assessed the effect of the BCA Bacillus thuringiensis (Bt) on the microbial communities within the pepper plant phyllosphere using culture-independent methodologies. Phospholipid fatty acid (PLFA) analysis suggested that the bacterial and fungal biomass were not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 29 publications
0
37
0
1
Order By: Relevance
“…Previous studies, using plating and low-throughput molecular techniques, reported that the introduction of a biocontrol agent or a pathogen to the system had a marked impact on the plant microbiome (Teixidó et al, 1998;Zhang et al, 2008;BuddrusSchiemann et al, 2010;Chowdhury et al, 2013;Yin et al, 2013). Erlacher et al (2014) demonstrated shifts in the microbiota of lettuce as a result of introducing a pathogen (Rhizoctonia solani) and/or a biocontrol agent.…”
Section: The Role Of the Microbiome In Fruit Health And Disease à A Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies, using plating and low-throughput molecular techniques, reported that the introduction of a biocontrol agent or a pathogen to the system had a marked impact on the plant microbiome (Teixidó et al, 1998;Zhang et al, 2008;BuddrusSchiemann et al, 2010;Chowdhury et al, 2013;Yin et al, 2013). Erlacher et al (2014) demonstrated shifts in the microbiota of lettuce as a result of introducing a pathogen (Rhizoctonia solani) and/or a biocontrol agent.…”
Section: The Role Of the Microbiome In Fruit Health And Disease à A Nmentioning
confidence: 99%
“…Numerous reports have been published on various strategies and approaches that can be used to enhance the efficacy and reliability of postharvest biocontrol agents. These include combining biocontrol agents with use of salts and organic acids (Droby et al, 1997;Karabulut et al, 2001), glucose analogs (El Ghaouth et al, 2000), food additives Karabulut et al, 2003;Teixidó et al, 2001), and various physical treatments (Karabulut et al, 2002;Porat et al, 2002;Zhang et al, 2008). In most cases, enhanced efficacy was demonstrated using these approaches, however, each commodity-pathogen system has its own unique features and so specific protocols will need to commercially evaluated.…”
Section: Performance and Consistencymentioning
confidence: 99%
“…Biocontrol agents have been used to protect plants against foliar diseases in several crops (Yuen and Schoneweis, 2007;Alvindia and Natsuaki, 2008;Perello et al, 2007). However, many of them are poor competitors for leaf surface nutrients compared with indigenous phyllosphere microbes (Zhang et al, 2008a;Brandl, 2003, Lindow andLeveau, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various culture-independent methods such as phospholipid fatty acid analysis (PLFA) and 16S rRNA gene directed Polymerase Chain Reaction-Denaturing Gradient Gel Electrophoresis (PCR-DGGE) have been useful for detecting pollutant-induced changes in the composition of natural microbial communities (Morimoto et al, 2005;Chinalia and Killham, 2006;Ratcliff et al, 2006). PLFA results are interpreted based on the assumption that phospholipids make up a relatively constant proportion of the cell biomass and that variation in fatty acids among taxonomic groups can be used as biomarkers and the PLFA pattern of an environmental sample therefore reflects the microbial community composition (White et al, 1996;Zhang et al, 2008). PCR-DGGE separates 16S rRNA gene fragments based on differences to their resistance to chemical denaturation, generating a genetic profile of the individual bacterial species within a community (Burr et al, 2006;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…PLFA results are interpreted based on the assumption that phospholipids make up a relatively constant proportion of the cell biomass and that variation in fatty acids among taxonomic groups can be used as biomarkers and the PLFA pattern of an environmental sample therefore reflects the microbial community composition (White et al, 1996;Zhang et al, 2008). PCR-DGGE separates 16S rRNA gene fragments based on differences to their resistance to chemical denaturation, generating a genetic profile of the individual bacterial species within a community (Burr et al, 2006;Zhang et al, 2008). Applying such culture-independent methods to ecotoxicology studies may provide new insights into the pesticide-induced changes that occur to indigenous microbial communities of plants.…”
Section: Introductionmentioning
confidence: 99%